Immigration Policy Application in the Covid-19 Pandemic - Losandre, Bagoes; Ramadhan, Dewa; Basrian, Muhamad Rizki (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
Corona Virus Disease 2019 (Covid-19) was discovered in Wuhan, Hubei Province, China, at the end of 2019. Expansion into Indonesia. To combat the spread of Covid-19 in Indonesia, the Indonesian government, through the Directorate General of Immigration, has implemented a number of measures aimed at preserving fundamental freedoms. Concerning the extent to which mobility tactics are compatible with Covid-19 from the standpoint of fundamental freedom. Subjective and deductive reasoning are employed in the analysis. Thus, it was determined that the Indonesian government used many measures to address immigration issues during the Pandemic Covid-19 period, including limitations on outsiders entering Indonesia's territory and administrative restrictions. The research was used to evaluate how immigration policies were implemented during the Covid-19 pandemic era.